Rancang Bangun Sistem Ventilasi Vertikal Solar Adaptive pada Prototype Gedung Bertingkat Berbasis Mikrokontroler - Yanuar Enfika Rafani; Tibyani Tibyani; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Sunlight intensity of excess can causes problems apply temperature increase which resulted in inconvenience in the building. Therefore it takes a beam of sunlight in order to reduce or mitigate the heat and light from the Sun's entry into the building. By either using the arduino mega 2560 microcontroller and additional sensors LDR and DHT11 then vent can open or close a three-way, follow the direction of the Sun is high in the low sun and inside room temperature. Arduino Mega 2560 microcontroller implanted fuzzy sugeno logic as the output decision maker based on fuzzy calculation. The test results indicate various conditions the vent move the incoming light close based on the input from the sensors and sensors DHT11, LDR on fuzzy testing also obtained accurate results. This indicates the system is running properly in determining the motion of ventilation based from light angle.